How does the low-carbon city pilot policy affect the synergistic governance efficiency of carbon and smog? Quasi-experimental evidence from China. (1st November 2022) - Li, Zihao; Bai, Tingting; Tang, Chang
Abstract: In the context of the increasingly significant constraints of climate change and smog pollution on high-quality economic development in China, it is important to explore the impact of a low-carbon city pilot (LCCP) policies on the synergistic governance efficiency of carbon and smog (SGECS) for the realization of controlling peak carbon emissions and ensuring better air quality ("dual goals"). Based on the panel data of 216 cities in China from 2008 to 2018, the difference-in-difference (DID), propensity score matching-difference-in-difference (PSM-DID), and spatial difference-in-difference (SDID) methods are adopted to study the impact of LCCP on the SGECS. The study shows that 1) LCCP policies can significantly improve the SGECS, but the effect is not long-term and lasting. 2) Regarding the mechanism of action, LCCP policies can improve the SGECS by reducing energy consumption intensities and optimizing the industrial structure, but the mechanism of green technology innovation has not been effectively verified. 3) Regarding the extended analysis, LCCP policies have a more significant role in improving the SGECS in eastern and western cities and in cities with high levels of human and material resources. 4) Regarding the spatial spillover effects, LCCP policies have overall improvement effects on the SGECS in neighboring regions. However, the promotion effects of LCCP policies on the SGECS are mainly realized through the "competition for the top" among the pilot cities. The spatial spillover effect of the impact of LCCP policies on the SGECS gradually weakens with increasing geographical distance.